Financial Performance of Janapriya Multiple Campus Pokhara - Bhandari, Hari Bahadur (Janapriya Journal of Interdisciplinary Studies, 2018)
Financial performance analysis is based on financial statement. Financial statement is the final product of accounting process. Fundamentally, financial performance analysis refers to financial statement analysis to identify financial strength and weaknesses by establishing appropriate relationship among the figures of income statement and balance sheet. The main objective behind this study was to assess the financial performance of Janapriya Multiple Campus (JMC). Beside this, it also aimed to compare the financial performance and analyze the financial changes over a period of five years along with examining the cost recovery rate of JMC. This research was done with the help of secondary data entirely gathered from the annual report and official documents of the campus. The financial performance measured by using various financial/accounting and statistical tools such as common size financial statement, horizontal trend percent analysis, profitability ratios, mean and standard deviation. Based on the analysis, internal sources of fund including reserve and surplus, long term fund and campus development fund contribute more than 65% of the total liabilities/total assets. The highest percentage of permanent capital and fixed assets denote that the durable assets and fixed deposit amount were covered by the internal sources of fund. Findings have been arrived that the campus has got enough current assets to meet its current liabilities. The income statement shows total revenues increased every year at good rate and profit also increased every year except the years of 2070/71 and 071/72. In average, all profitability ratios are positive. Moreover, the analysis of collected data showed that there is no high fluctuation in the calculated profitability ratios and cost recovery rate. There exist positive relationship between revenue and expenses but the relationship is insignificant. Revenue explains 52.3 percent variation of variation in expenses. However, the institution is financially viable and there is a strong possibility to make money in long run.